Aerobic bacteria associated with chronic suppurative otitis media in Angola - Fabian Uddén; Matuba Filipe; Åke Reimer; Maria Paul; Erika Matuschek; John Thegerström; Sven Hammerschmidt; Tuula Pelkonen; Kristian Riesbeck (BMC, 2018)
Abstract Background Chronic suppurative otitis media (CSOM) is an important cause of hearing loss in children and constitutes a serious health problem globally with a strong association to resource-limited living conditions. Topical antibiotics combined with aural toilet is the first-hand treatment for CSOM but antimicrobial resistance and limited availability to antibiotics are obstacles in some areas. The goal of this study was to define aerobic pathogens associated with CSOM in Angola with the overall aim to provide a background for local treatment recommendations. Methods Samples from ear discharge and the nasopharynx were collected and cultured from 152 patients with ear discharge and perforation of the tympanic membrane. Identification of bacterial species was performed with matrix-assisted laser desorption/ionization-time of flight mass spectrometry and pneumococci were serotyped using multiplex polymerase chain reactions. Antimicrobial susceptibility testing was done according to EUCAST. Results One hundred eighty-four samples from ear discharge and 151 nasopharyngeal swabs were collected and yielded 534 and 289 individual isolates, respectively. In all patients, correspondence rate of isolates from 2 ears in patients with bilateral disease was 27.3% and 9.3% comparing isolates from the nasopharynx and ear discharge, respectively. Proteus spp. (14.7%), Pseudomonas aeruginosa (13.2%) and Enterococcus spp. (8.8%) were dominating pathogens isolated from ear discharge. A large part of the remaining species belonged to Enterobacteriaceae (23.5%). Pneumococci and Staphylococcus aureus were detected in approximately 10% of nasopharyngeal samples. Resistance rates to quinolones exceeded 10% among Enterobacteriaceae and was 30.8% in S. aureus, whereas 6.3% of P. aeruginosa were resistant. Conclusions The infection of the middle ear in CSOM is highly polymicrobial, and isolates found in nasopharynx do not correspond well with those found in ear discharge. Pathogens associated with CSOM in Angola are dominated by gram-negatives including Enterobacteriaceae and P. aeruginosa, while gram-positive enterococci also are common. Based on the results of antimicrobial susceptibility testing topical quinolones would be the preferred antibiotic therapy of CSOM in Angola. Topical antiseptics such as aluminium acetate, acetic acid or boric acid, however, may be more feasible options due to a possibly emerging antimicrobial resistance.